Appendix D to "Systems engineering competencies and proficiency levels by role for an MBSE-enabled project" - Shaw, Sarah G., author (Colorado State University. Libraries, 2025)
Appendix D contains radar plots showing the required proficiency level in each competency in the Digital Engineering Competency Framework (DECF) v1.1 for each role in the System Requirements Definition and Traceability project.
Paper submitted for publication to the IEEE Open Journal of Systems Engineering, October 2025.
Keywords: model-based systems engineering (MBSE); digital engineering (DE); digital engineering competency framework (DECF); systems engineering (SE)